Product Knowledge Analysis of Mobile Banking on the Use of Mobile Banking and Saving Behavior - Mallombasang, Andi Dewi Aulia; Ismail, Muhamad; Dewi, Andi Ratna Sari (Pascasarjana STIE Amkop Makassar, 2020)
This study aims to find out the influence of product knowledge on the utilization of mobile banking and saving behavior on millennial customers of PT Bank Negara Indonesia Makassar Region either directly or indirectly. This research is a quantitative research using questionnaires, interviews, documentation and observations to collect data related to variables that have been determined and then processed using the help of SmartPLS 3.2.8 software. The results of the study found that product Knowledge variables partially affect the positive and significant effect on mobile banking in millennial customers of PT Bank Negara Indonesia Makassar Region. Then the product knowledge variable partially affects the positive and significant effect on saving behavior at PT Bank Negara Indonesia Makassar Region. Then mobile banking variables partially affect the positive and insignificant effect on the behavior of saving in millennial customers of PT Bank Negara Indonesia Makassar Region and lastly product knowledge variables have a positive and insignificant effect on saving behavior if through the use of mobile banking on millennial customers of PT Bank Negara Indonesia Region.